Incidence and predictors of mortality among adolescents on antiretroviral therapy in Amhara Region, Ethiopia: a retrospective cohort analysis. Issue 11 (9th November 2022) - Leshargie, Cheru Tesema; Demant, Daniel; Burrowes, Sahai; Frawley, Jane
Abstract : Objective: This study aimed to assess the incidence and predictors of mortality in adolescents receiving antiretroviral therapy (ART) in Ethiopia's Amhara Region. Design: We conducted an institution-based retrospective follow-up study. Settings: The study was conducted at Amhara Region's comprehensive specialised hospitals in Ethiopia. Participants: We included 961 randomly selected medical records of adolescents receiving ART between January 2005 and June 2020. Primary and secondary outcomes: The incidence of mortality since ART treatment initiation served as the primary outcome, and predictors of mortality served as secondary outcomes. We used Cox proportional hazard regression to examine the relationship between mortality and its predictors. Variables with p values<0.05 in the multivariable analysis were considered statistically significant mortality predictors. Adjusted HR (aHR) with 95% CI was used to measure the strength of association. Results: More than half (n=496, 53.5%) of the adolescents living with HIV (ALHIV) were girls. The adolescent mortality rate was 1.52 (95% CI: 1.04 to 1.53) per 100 person-years throughout the follow-up period of 81 583 adolescent months. Mortality was higher for ALHIV who had not received formal education (aHR: 3.27, 95% CI: 1.36 to 7.87), had widowed parents (aHR: 1.85, CI: 95% 1.01 to 3.56) or received no social support (aHR: 2.81, 95% CI: 1.69 to 4.67). Adolescents who had opportunistic infections (OIs) at ART initiation (aHR: 1.94, 95% CI: 1.19 to 3.14), low haemoglobin (Hgb/g/l) levels (aHR: 2.17, 95% CI: 1.08 to 4.18), a bedridden functional status (aHR: 3.11, 95% CI: 1.64 to 5.72), stage IV clinical staging (aHR: 3.03, 95% CI: 1.46 to 6.30), non-disclosing status (aHR: 2.24, 95% CI:1.36 to 3.69) and CD4 count 200–350 cells/mm 3 (aHR: 2.17, 95% CI: 1.08 to 4.18) also had a higher risk of death. Not receiving cotrimoxazole preventive therapy (aHR: 1.85, 95% CI: 1.07 to 3.22) and poor adherence to ART (aHR: 2.24, 95% CI: 1.27 to 3.95), compared with adherent, was associated with higher mortality risk. Changed treatment regimens were associated with lower mortality (aHR: 0.59, 95% CI: 0.35 to 0.98). Conclusions: Our study found a lower mortality rate for adolescents with HIV than previous Ethiopian studies, but our significant mortality predictors were similar to those found in earlier studies of adults and adolescents. Our findings reveal a potential point for health service improvement in Ethiopia: incorporating monitoring of Hgb levels into patient follow-up care, supporting recommendations that clinicians emphasise managing OIs and providing counselling services to improve adherence.